2013
DOI: 10.1177/0731684413500545
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of bio-fibers-reinforced high-density polyethylene composites: effect of coupling agents and bio-fillers

Abstract: Bio-based fibers (wood and bamboo)-filled high-density polyethylene composites were prepared in a twin-screw extruder using two types of coupling agents: maleated polyethylene and glycidyl methacrylate-grafted polyethylene. The effect of bio-fibers used as filler on the mechanical properties of composites was studied. It was observed that mechanical properties such as tensile and flexural strengths of the composites with coupling agent increased with increasing filler loadings. Tensile strength and flexural st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…MAPE covalently couples PE and fibers [20]. Studies that included 5 wt% of MAPE to coupling PE with bamboo fibers showed increases in flexural and tensile strength [21], respect to the composite without compatibilizer. Yuan et al [22] used only 3 wt% of MAPE as compatibilizer between PE and fibers of maple wood and found that the use of the coupling agent increased the tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…MAPE covalently couples PE and fibers [20]. Studies that included 5 wt% of MAPE to coupling PE with bamboo fibers showed increases in flexural and tensile strength [21], respect to the composite without compatibilizer. Yuan et al [22] used only 3 wt% of MAPE as compatibilizer between PE and fibers of maple wood and found that the use of the coupling agent increased the tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of its bifunctionality, the compatibilizer is assumed to increase adhesion between wood and plastic. Maleated polyethylene (MAPE) increases the tensile and flexural strengths of the resulting composite material [ 18 , 19 , 20 ]. In composites made with polyethylene, it is the most widely used compatibilizer [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…These types of fillers have been processed with polyethylene, polypropylene, PVC and ABS systems in which processing temperatures are lower than their degradation temperatures . Among those studies performed with wood flour were more popular due to its environmentally benign character .…”
Section: Introductionmentioning
confidence: 99%